PENGARUH HRM PRACTICE, INDIVIDUAL INNOVATION DAN JOB SATISFACTION TERHADAP EMPLOYEE PERFORMANCE DIMEDIASI OLEH HRIS USAGE - Sinaga, Windy Saroh; Meilani, Yohana F. Cahya Palupi (Creative Research Management Journal, 2024)
This study aims to determine the effect of human resource management practices, individual innovation capability, and job satisfaction on employee performance, with HRIS usage as a mediator. A cross-sectional method was used to obtain quantitative data through an online questionnaire, adapted from existing questions in previous literature. Data were collected from all members of the target population, consisting of 69 non-managerial HR division employees at private company XYZ, who had worked for at least one year, using a census or saturation sampling technique. The data were then analyzed using PLS-SEM software. The results showed a significant relationship between human resource management practices, individual innovation capability, job satisfaction, and HRIS USAGE on employee performance. However, HRIS USAGE did not mediate the relationship between human resource management practices, individual innovation capability, job satisfaction, and employee performance among HR division employees at private company XYZ. This study was only empirically tested within the HR division using saturated sampling or a census approach, resulting in limitations in the generalizability of the findings. These findings offer managerial implications that can help private company XYZ improve employee performance.